Response kinetics in the complex chemotaxis signalling pathway of Rhodobacter sphaeroides. - Kojadinovic, M; Armitage, J; Tindall, M; Wadhams, G (2013)
Chemotaxis is one of the best-characterized signalling systems in biology. It is the mechanism by which bacteria move towards optimal environments and is implicated in biofilm formation, pathogenesis and symbiosis. The properties of the bacterial chemosensory response have been described in detail for the single chemosensory pathway of Escherichia coli. We have characterized the properties of the chemosensory response of Rhodobacter sphaeroides, an α-proteobacterium with multiple chemotaxis pathways, under two growth conditions allowing the effects of protein expression levels and cell architecture to be investigated. Using tethered cell assays, we measured the responses of the system to step changes in concentration of the attractant propionate and show that, independently of the growth conditions, R. sphaeroides is chemotactic over at least five orders of magnitude and has a sensing profile following Weber's Law. Mathematical modelling also shows that, as E. coli, R. sphaeroides is capable of showing fold-change detection (FCD). Our results indicate that general features of bacterial chemotaxis such as the range and sensitivity of detection, adaptation times, adherence to Weber's Law and the presence of FCD may be integral features of chemotaxis systems in general, regardless of network complexity, protein expression levels and cellular architecture across different species.